What do unions do in China? - Ge, Ying (Bejing, 2007)
This paper is the first to use a large micro - level data set to investigate the activities and effectiveness of Chinese unions. We show that Chinese unions have a strong State - Party voice face and a collective voice face but lack a monopoly face. The empirical findings on the effectiveness of unions are remarkable: the presence of unions in the workplace is positively related to average wage and benefit levels, productivity, research and development investment and human capital investment, but negatively related to enterprise profitability. The unions in China do have real effects.